2010
DOI: 10.1177/2150131910361360
|View full text |Cite
|
Sign up to set email alerts
|

Is Appropriate Management of Atrial Fibrillation in Primary Care a Utopia?

Abstract: Shortages and limitations of the peripheral or rural units and health centers and inadequate knowledge and application of the guidelines, seemed to be major factors responsible for mismanaging AF patients. More education in prehospital cardiology may contribute in improving management of arrhythmias in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Limited provider knowledge and resources have been identified as contributors to poorer AF management in rural communities. 6 Other studies have found that patients admitted to rural hospitals for AF had a 17% greater risk of death compared to urban centers, and elderly patients in rural areas are 12% less likely to receive antithrombotic therapy despite having significantly fewer relative contraindications. 7,9 To our knowledge, no specific intervention has demonstrated the potential to bring AF care to under-resourced communities by elevating the level of care using embedded primary care providers.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Limited provider knowledge and resources have been identified as contributors to poorer AF management in rural communities. 6 Other studies have found that patients admitted to rural hospitals for AF had a 17% greater risk of death compared to urban centers, and elderly patients in rural areas are 12% less likely to receive antithrombotic therapy despite having significantly fewer relative contraindications. 7,9 To our knowledge, no specific intervention has demonstrated the potential to bring AF care to under-resourced communities by elevating the level of care using embedded primary care providers.…”
Section: Discussionmentioning
confidence: 97%
“…1,4,5 Moreover, rural and under-resourced regions are disproportionately affected by sub-optimal care due to resource limitations and inadequate access to community providers with specialized training in AF, resulting in greater non-adherence to clinical guidelines, underutilization of stroke prophylaxis, and higher rates of in-hospital mortality compared to urban communities. [6][7][8][9][10] Primary care providers are often the sole providers serving these vulnerable patient populations and may have difficulty gaining confidence in AF care as management recommendations become increasingly complex. Disparities of access to specialty AF care may be more adequately addressed through engaging with primary care providers who can become local AF care partners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests geographic variation in AF care with some evidence showing inequitable care for those in rural communities [5]. Evidence shows that rural older adults with AF receive primary care that does not consistently meet clinical guidelines [6] and have overall higher in-hospital mortality rates compared to their hospitalized urban counterparts [7]. Although not mandated, many rural patients may never see a cardiologist or have an echocardiogram [8].…”
Section: Introductionmentioning
confidence: 99%
“…It creates challenges for providers working in rural communities who are already faced with workload issues, blurring of personal and professional boundaries, isolation, and lack of professional development opportunities (Buykx et al, 2010). Research demonstrates rural older adults with AF experience breaks in continuity of care when hospitalized outside their communities (Biem et al, 2003), receive primary care failing to meet guidelines (Lygidakis et al, 2010), and may never have seen a cardiologist or had an echocardiogram ( Jordan et al, 2011). Compared to their urban counterparts, rural older adults with AF receive less antithrombotic therapy (Kakkar et al, 2013) despite having similar risks for stroke and bleeding (Tsadok et al, 2015).…”
Section: Introductionmentioning
confidence: 99%